Nb2O5–Ni3N heterojunction tuned by interface oxygen vacancy engineering for the enhancement of electrocatalytic hydrogen evolution activity. Issue 19 (13th April 2021) - Chen, Xiao Hui; Li, Xiao Lin; Wu, Li Li; Fu, Hong Chuan; Luo, Juan; Shen, Li; Zhang, Qing; Lei, Jing Lei; Luo, Hong Qun; Li, Nian Bing
Abstract : Ni3 N is combined with Nb2 O5 to form an interfacial oxygen vacancy induced Nb2 O5 –Ni3 N/NF heterojunction to improve the catalytic performance of Ni3 N for the hydrogen evolution reaction. Abstract : The requirement of hydrogen adsorption Gibbs free energy (Δ G H* ) approximating to 0 eV limits the hydrogen evolution reaction (HER) activity of most electrocatalysts in alkaline media. The construction of interface and defects engineering is an effective strategy to obtain the optimal Δ G H* . Ni3 N exhibits poor HER activity due to its undesirable Δ G H* . By cooperating with Nb2 O5, the d-band center of Ni3 N was reduced, improving its catalytic performance. The optimized Nb2 O5 –Ni3 N displays an overpotential of 80 mV at 10 mA cm −2 and superior activity than the benchmark Pt/C catalyst when the current density is greater than 125 mA cm −2 . Experimental and density functional theory results demonstrate that the improved catalytic activity is because the electronic interaction between Ni and Nb changes the coordination numbers of these two atoms, resulting in oxygen vacancies at the interface. Under the synergistic effect of Nb2 O5 and Ni3 N, the catalyst exhibits optimal Δ G H* and water adsorption energy.